DAMPAK NUKLIR KOREA UTARA TERHADAP SECURITY DILEMMA DI ASIA TIMUR - Fatturrahman . (SPEKTRUM, 2012)
Abstract North Korean nuclear program gave a serious threat over security level in East Asia after Cold War. The highly strong arm race of this region makes it dangerous for stabilizing on international security, particularly in the Eat Asia. One of the most important things of arm race effect is security dilemma in this region. The US and Russia are two powerful actors in the political and security landscape in the world which can modify security map in the East Asia. Japan and South Korea are regional alliance of US, while North Korea is Russia alliance. Both US and Russia will support and keep its influence although the Cold War ended. Keywords: North Korean Nuclear, security dilemma, US, and Russia.